MEKANISME UJARAN DALAM BAHASA ARAB; TINJAUAN PSIKOLINGUISTIK - Nasution, Sahkholid (Universitas Nurul Jadid, 2014)
Speech is the key to realize the spoken language. Because oral language is the process of conveying the meaning by the speaker to the listener through one or a series of speechs. Speech can be produced through the complex process of articulation. Said to be complex, because it requires the cooperation between the flow of breath, vocal cords and tools of articulation. The process of speech applies to all languages, including Arabic language. Nevertheless, many of the students in Indonesia when learning Arabic language feel difficulty in articulating the words of Arabic language properly. Therefore, it is necessary to analyze the sound of Arabic language created by the concept of mechanism of speech in the language in general, to assist the difficulties faced by students in learning Arabic language.